LINGUISTIC BARRIERS ENCOUNTERED IN THESIS WRITING BY STUDENTS OF THE SHARIA ECONOMICS PROGRAM AT INSTITUT 'AISYIYAH SULAWESI SELATAN - Dirmawati (Indonesian language and literature education program Majapahit Islamic University, 2025)
Thesis writing is one of the essential stages in completing undergraduate studies, including for students of the Sharia Economics Department. However, many students face linguistic challenges that affect the clarity and quality of the scientific work produced. This research seeks to uncover and examine the linguistic challenges present in the theses written by Sharia Economics students at the Parahikma Indonesia Institute. The method used is descriptive qualitative, employing documentation techniques on 21 thesis manuscripts as the sample. The findings indicate that errors in diction, sentence structure, paragraph coherence, and idea organization are the main challenges. These results highlight the need for more intensive and contextual academic writing training that aligns with the terminology used in sharia economics. Keywords: language, thesis, sharia economics, academic writing, students